HUBUNGAN GRAVIDA DENGAN TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III - Enok Nurliawati; Etty Komariah Sambas; Betty Suprapti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The third trimester of pregnancy is 29 weeks to 40 weeks of gestation, which is the preparation period for giving birth. The anxiety of pregnant women during this period is due to concerns about the end of the pregnancy and the birth process in addition to changing responsibilities as a mother when the baby is born. Primigravida mothers tend to experience anxiety because they do not have the experience to get through these periods. This research aimed to determine the correlation between gravida and anxiety levels in third-trimester pregnant women. This research used a correlational quantitative design. The number of respondents was 51 people using the total sampling technique. The instrument was a questionnaire adapted from the Hamilton Anxiety Rating Scale (HARS). Data analysis used Spearman rank. The study results showed that there was a relationship between gravida and anxiety in the third-trimester pregnant women with a strong relationship and a negative correlation direction (p-value 0.001, r = -0.516, α = 0.05). This shows that the lower the gravida, the higher the level of anxiety.